A Comparison of Large Soft Palate Defect Reconstruction Using the New “Tunnel Structure” and Traditional “Port Structure” Methods - Hamahata, Atsumori; Beppu, Takeshi; Tokumaru, Takao; Yamaki, Takashi; Sakurai, Hiroyuki (Journal of Reconstructive Microsurgery, 2017)
Background For soft palate defects of more than two-thirds, we previously described the bent anterolateral thigh (ALT) method in which the pharyngeal isthmus was reconstructed as a tunnel structure. In this study, we compared the new “tunnel structure” reconstruction in our bent ALT flap method and the traditional “port structure” reconstruction.Methods From April 2010 to March 2015, 25 patients in Saitama Cancer Center (Saitama, Japan) underwent oropharyngeal tumor resection including soft palate resection. In patients who had soft palate resection of less than two-thirds, the Gehanno method was performed in 10 patients (the data were shown as a comparison). In patients who had soft palate resection of more than two-thirds, the pharyngeal isthmus was reconstructed as a tunnel structure using the bent ALT flap method in eight patients and as a port structure in seven patients. The functional outcomes were assessed by interviewing patients about their symptoms and measuring the standard articulation test.Results Postoperative function was favorably maintained at equal levels in the tunnel structure reconstruction group and the Gehanno method group at approximately 12 months postoperation. However, in most patients in the port structure reconstruction group, the pharyngeal isthmus became larger after 12 months postoperation and the articulation test was significantly worse than the Gehanno group and the tunnel group.Conclusion The bent ALT flap method had superior results to the conventional method. Thus the pharyngeal isthmus should be reconstructed as a tunnel structure for patients with soft palate defects of more than two-thirds.
Keywords: oropharyngeal reconstruction; velopharyngoplasty; Anterolateral thigh flap